The Idea of the Application of Senses in Meditations about The Passion Exemplified in a Manuscript Stored at Archive of the Sisters of St. Norbert’s Order in Zwierzyniec (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
This article presents the method of the application of senses presented in anonymous meditationsentitled Kontemplacja Męki i śmierci Chrystusa Pana. The manuscript dates back to the XVII century andis stored in the archives of the Sisters of St. Norbert’s Order in Cracow, so it is possible to make the thesisthat the author of this manuscript belonged to this abbey. Contained in the manuscript are meditationsthat induce contemplation of The Passion with accommodation of the senses, the method introducedby Ignatius of Loyola, and with co-operation of three spiritual rules: the memory, intellect, and volitionin meditation of circumstances of Christ’s life and mysteries of faith. Upon the conception of the fivespiritual senses wrote Origen as well as Saint Bonaventure.In the anonymous manuscript the method of application of senses are used mainly in meditationsabout Christ’s Agony in the Garden, the flagellation, Saint Mary’s feelings during Christ’s lashing, thecrowning of thorns and crucifixion. The meditations advice precise “observation” by seeing, hearing,smell, feeling and taste of the suffering of Christ. The article submits that all senses used in meditations inthe proper way conduce not only to better knowledge of disclosed laws but also to the regular officiatingof spiritual exercises and to interior improvement.